Home > Geometry, Triangles > Pythagoras’ Theorem

Pythagoras’ Theorem

Definition: The square of the hypotenuse is equal to the sum of the squares of the other two sides.

Proof

Right angled triangle with squares

What this means is that if we draw three squares where the length of the sides of the squares are equal to the lengths of the sides of the triangle the area of the big square equals the area of the two smaller squares added together.  (note: The hypotenuse is opposite the right angle and this side produces the largest square)

In the diagram above the largest square is the green square so this implies that c^2=a^2+b^2

It follows that if we are finding a shorter side then we could use a^2=c^2-b^2

Examples

Find the length of the hypotenuse.

Question

Here a=3\mbox{ and }b=7

So using c^2=a^2+b^2

We get c^2=3^2+7^2=58

\implies c=\sqrt{58}=7.62cm


Find the length of the missing side 

Question

Since we are finding one of the shorter sides we will use a^2=c^2-b^2

Here b=4\mbox{ and }c=12

We get a^2=12^2-4^2=128

\implies a=\sqrt{128}=11.31cm


Find the value of xThis is a right-angled triangle so let’s use c^2=a^2+b^2 

Question

\implies 50^2=x^2+(2x)^2

\implies 2500=5x^2

\implies x^2=500

\implies x=\sqrt{500}=22.36mm


Does 11cm, 59cm, 60cm produce a right-angled triangle?Use c^2=a^2+b^2 where c=60 since that is the longest length. 

\implies 60^2=11^2+59^2

But 3600\neq 3602, therefore this is not a right-angled triangle.

Questions

Advertisements
Categories: Geometry, Triangles
  1. No comments yet.
  1. No trackbacks yet.

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

%d bloggers like this: